Respiratory System of Rhodotorula glutinis I. Inhibitor Tolerance and Cytochrome Components - Matsunaka, Shooichi (1966)
Oxygen uptake by the carotenoid-containing yeast, Rhodotorula glutinis was not affected by concentrations of cyanide and antimycin A which completely inhibit the respiration of Saccharomyces cerevisiae. The tolerance of R. glutinis to these inhibitors was somewhat dependent on the age of the cultures. Reduced minus aerated difference spectra of cells revealed spectral changes presumably due to cytochromes and carotenoids. The kinetics of these spectral changes induced by oxygen were followed. Carotenoid deficient cells were prepared by growth in the presence of diphenylamine. Difference spectra of these cells revealed the presence of flavoprotein, and a, b, and c type cytochromes. Growth of R. glutinis was completely inhibited by concentrations of cyanide which did not affect respiration. Oxidation of reduced nicotinamide adenine dinucleotide by sub-cellular fractions was sensitive to cyanide and antimycin A. Although respiration of intact cells is tolerant to these inhibitors, studies with cell-free extracts suggest the presence of a cyanide and antimycin A-sensitive, cytochrome-linked, respiratory chain.